2019
DOI: 10.1111/aos.14076
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of retinal and choroid capillary ischaemia using optical coherence tomography angiography in type 2 diabetes

Abstract: Purpose: To perform a quantitative analysis of retinal and choroid capillary ischaemia in diabetic patients by using optical coherence tomography angiography (OCTA). Methods: A total of 97 type 2 diabetic patients and 48 controls were included in this cross-sectional study. Diabetic patients without diabetic retinopathy (DR) were categorized as no DR (NDR) group; DR was classified into mild nonproliferative diabetic retinopathy (NPDR), moderate NPDR, severe NPDR and proliferative diabetic retinopathy (PDR). Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 28 publications
5
30
1
1
Order By: Relevance
“…Previous OCTA studies have shown that vessel density (VD) and FAZ were correlated with the course of disease and visual results in some retinal diseases. Along with the severity of diabetic retinopathy and the decline of visual acuity (VA), Li et al [8] revealed a chronological development of microvascular ischemia, from the choroid layer toward DCP and SCP with a gradually decreased VD. Nelis et al [9] found that the VD ratio based on OCTA could serve as an indicator of capillary architecture changes, which was associated with the degree of epiretinal membrane extraction.…”
Section: Introductionmentioning
confidence: 99%
“…Previous OCTA studies have shown that vessel density (VD) and FAZ were correlated with the course of disease and visual results in some retinal diseases. Along with the severity of diabetic retinopathy and the decline of visual acuity (VA), Li et al [8] revealed a chronological development of microvascular ischemia, from the choroid layer toward DCP and SCP with a gradually decreased VD. Nelis et al [9] found that the VD ratio based on OCTA could serve as an indicator of capillary architecture changes, which was associated with the degree of epiretinal membrane extraction.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed reduced perfusion in the retinal vessels and choriocapillaris in diabetic eyes with and without retinopathy and this reduced perfusion originated from the choroid and spread to the retinal vessels 33–36 . A recent study showed that in diabetic patients, the change in retinal vasculature preceded the tomographic changes 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed reduced perfusion in the retinal vessels and choriocapillaris in diabetic eyes with and without retinopathy and this reduced perfusion originated from the choroid and spread to the retinal vessels. [33][34][35][36] A recent study showed that in diabetic patients, the change in retinal vasculature preceded the tomographic changes. 37 The study showed that choroidal thickness, vessel density of superficial and deep OCTA layer indicated early changes in DWR Note: Median and its 95% confidence interval is provided below.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of excellent studies that have highlighted the potential power of OCT-A in discriminating diabetic status. [17][18][19][20][21] In particular, pioneering work by Durbin et al 7 demonstrated the ability of measuring retinal microvasculature to distinguish diabetic status in patients. In their albeit small cohort they demonstrated highest area under the ROC curve (i.e., AUC) of 0.893 for measures of the vessel density in the superficial capillary network.…”
Section: Discussionmentioning
confidence: 99%